PVSYST-Based Solar Power Plant Planning - Anrizal Akbar, Muhammad Alif; Yunus, A.M Shiddiq; Tangko, Jumadi (INTEK: Jurnal Penelitian, 2022)
This research uses the PVSyst software which can plan an off-grid SPP system and find out how much electricity is generated in the Auditorium Building Campus 2, Ujung Pandang State Polytechnic. PVSyst is a software package that is used for the learning process, sizing, and data analysis of the PV mini-grid system. PVSyst is divided into grid connected systems, standalone systems, pumping systems. PVSyst is also equipped with a database from a wide and diverse range of meteorological data sources, as well as data on PV mini-grid components. In planning a PVSyst-based solar power plant, it can be used to find out how much electrical energy is generated to meet the electricity needs of the Campus 2 Auditorium Building, Ujung Pandang State Polytechnic. In this study using the PVSyst software according to the proposed load requires an average energy of 482 kWh/day, therefore, the panel module used is the polycrystalline type model CS3W-410P-HE manufacturer Canadian Solar Inc, where each panel unit used has a nominal power of 410 WP requires 422 modules, 2 modules in series and 211 modules in parallel. The battery used is a lead acid type with a 12-CS-11PS model manufactured from Rolls. The batteries used are 195 batteries, of which 3 batteries are installed in series and 64 batteries are installed in parallel. The controllers needed in this design are 50 units with the FLEXmax 80-36V model manufactured from Outback. The technology of this controller is an MPPT converter. In planning Solar Power Plant using PVSyst in the Auditorium Building Campus 2 of Ujung Pandang State Polytechnic, it produces electricity of 227,122 kWh per year.